Analısıs Perhıtungan Struktur Pelat Lantaı Pada Proyek Pembangunan Gedung Solnet - Risky Bayu Pratomo; Mahfuz Hudori (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Floor slabs are building structural components that have certain dimensions to transmit dead loads and live loads on them to be distributed to the supports. floor slab calculations must be accurate. This study aims to determine the reinforcement of floor slabs in the Solnet Building construction project, Batam City. The results of the analysis show that the floor slab structure using a floor slab thickness of 110 mm with steel reinforcement with a diameter of 10 mm and a distance between iron of 300 mm consisting of two layers is able to withstand a dead load of 4,18 kN/m2 and a live load of 2 kN/m2.